Field comparison of a roof bolter dry dust collection system with an original designed wet collection system for dust control - Reed, W. R. (Min Metall Explor, 2020)
Dust collectors for roof bolting machines generally use a dry box to collect the roof bolting material. Recently, an underground mining operation converted a dry box dust collector to a wet box dust collector with a unique exception from MSHA for testing purposes. Water is routed to the roof bolter from the main water line of the continuous miner. The wet box utilizes a water spray to wet the incoming material. Testing was conducted comparing the two different collector types. Respirable dust concentrations surrounding the roof bolter with the different collection boxes were similar. The main difference in respirable dust concentrations occurred when cleaning the dust boxes. The average respirable dust concentration during cleaning of the wet box was 0.475 mg/m(3), and during the cleaning of the dry box, the average respirable dust concentration was 1.188 mg/m(3), a 60% reduction in respirable dust concentration. The quartz content of the roof material was high, ranging from 28.9 to 52.7% during this study. The results from this study indicate that using the wet box as a collector reduced exposure to respirable dust up to 60% when cleaning the collector boxes.